Evaluating Effectiveness, Safety, and Patient Outcomes of 3D Printing in Orthopedic Implant Design and Customization: A PRISMA-Complaint Systematic Review - Mainak Roy; Madhan Jeyaraman; Naveen Jeyaraman; Arpit Sahu; Sanjeevi Bharadwaj; Abhijith K Jayan (Journal of Orthopaedic Case Reports)
Introduction: The advent of 3D printing technology has revolutionized the field of orthopedics, particularly in the design and customization of implants. This study aims to evaluate the effectiveness, safety, and patient outcomes associated with the use of 3D-printed custom implants for various orthopedic conditions. Materials and Methods: The systematic review was registered in PROSPERO (CRD42025648097). The literature search analyzed studies from multiple databases, focusing on parameters, such as implant fit, functionality, surgical outcomes, and patient satisfaction. Studies were selected based on their relevance to 3D-printed custom implants for various orthopedic conditions. Results: The analysis included data from numerous studies, highlighting several key findings, such as (a) customization: 3D-printed implants provide a highly personalized fit that conforms precisely to individual anatomies, enhancing biomechanical performance and reducing complications, (b) surgical outcomes: The use of 3D-printed implants significantly reduces surgery time and intraoperative errors due to advanced imaging and meticulous pre-operative planning, (c) patient satisfaction: Patients reported higher satisfaction rates due to improved implant stability and functionality, leading to quicker recovery and a better quality of life post-surgery, and (d) challenges: The high costs of 3D printing technology and concerns about the long-term durability and performance of 3D-printed implants remain significant barriers to widespread adoption. Conclusion: The integration of 3D printing technology into orthopedic implant design represents a transformative advancement, offering significant improvements in patient-specific outcomes and surgical precision. Despite financial and technical challenges, the potential benefits of delivering personalized, high-quality care are substantial. Future research should focus on long-term follow-up studies to provide comprehensive evidence on the safety and durability of 3D-printed implants, and efforts should be made to reduce production costs and streamline manufacturing processes to enhance accessibility. Level of Evidence: Systematic review and meta-analysis, Level II.